Mechanisms for Promoting Health Tourism Sites in Egypt: Towards the Development of Sustainable Specialized Urban Cities with a Competitive Brand - Mohamed Riad (JES: Journal of Engineering Sciences)
The research seeks in the context of modern global trends in the health tourism industry, and to achieve the goals of "Vision Egypt 2030" for sustainable development, and to enhance the position of Egypt on the global health tourism map, the research addresses the future of the health tourism industry in Egypt, with a focus on identifying opportunities and risks to activate this sector effectively and sustainably, and benefit from the experiences of successful countries such as the UAE, Thailand and Singapore, especially India with the slogan (quality, transparency and service) and the promotional slogan for it is to address the first world at third world prices,The research proposes the establishment of cities with an urban environment specialized in health tourism that provide comprehensive medical and health services to patients and those looking for comprehensive distinctive health experiences in one place, by combining the medical and scientific aspect and the comprehensive preventive approach to reach the appropriate strategy and action plan, to promote health tourism and increase its revenues in a short time, which contributes to the establishment of a sustainable built environment with a brand and global competitiveness that benefits the national economy ,The research focuses on places with the elements of health tourism in Egypt. The research is an inductive and analytical approach, in order to reach a sound analysis of the health tourism market globally and locally, and the research is expected to provide specific recommendations to support this promising and growing sector in the Egypt.